1997
DOI: 10.1093/carcin/18.5.1085
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of aromatic amines by human pancreas

Abstract: Epidemiologic studies have suggested that aromatic amines (and nitroaromatic hydrocarbons) may be carcinogenic for human pancreas. Pancreatic tissues from 29 organ donors (13 smokers, 16 non-smokers) were examined for their ability to metabolize aromatic amines and other carcinogens. Microsomes showed no activity for cytochrome P450 (P450) 1A2-dependent N-oxidation of 4-aminobiphenyl (ABP) or for the following activities (and associated P450s): aminopyrine N-demethylation and ethylmorphine N-demethylation (P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 14 publications
3
49
0
Order By: Relevance
“…There was no stacking between IQ and C 6 or C 8 . The observed NOEs (Table S4 in the Supporting Information) were consistent with the IQ H4A and H5A protons being directed toward C 18 and G 19 in the complementary strand, and the IQ H7A, H8A, and H9A protons being directed toward G 17 and C 18 in the complementary strand (Figure 10). The IQ methyl protons were closer to G 19 than to C 8 (Figure 10), also consistent with the observed NOEs (Table S4).…”
Section: Base-displaced Insertion Of the Iq Adductsupporting
confidence: 64%
See 3 more Smart Citations
“…There was no stacking between IQ and C 6 or C 8 . The observed NOEs (Table S4 in the Supporting Information) were consistent with the IQ H4A and H5A protons being directed toward C 18 and G 19 in the complementary strand, and the IQ H7A, H8A, and H9A protons being directed toward G 17 and C 18 in the complementary strand (Figure 10). The IQ methyl protons were closer to G 19 than to C 8 (Figure 10), also consistent with the observed NOEs (Table S4).…”
Section: Base-displaced Insertion Of the Iq Adductsupporting
confidence: 64%
“…The downfield 31 P chemical shift at P 6 presumably reflects conformational perturbations associated with the P 6 phosphodiester. 84 The small differences observed for 31 P chemical shifts for P 17 and P 18 suggested that the phosphodiesters opposite to X 7 in the complementary strand were less perturbed. The carcinogen-base linkage site at X 7 residue is defined by the torsion angles α′…”
Section: Torsion Angle Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Approximately 46% of NNN and 26%-37% of NNK in tobacco is preformed and the remainder is pyrosynthesized from nicotine during smoking (36). Other harmful constituents of tobacco smoke include polycyclic aromatic hydrocarbons (PAHs), although their role in pancreatic disease remains unclear (7,36). In the following sections we will report the general effects of tobacco on the pancreas and subsequently focus on nicotine and NNK, since they are the most studied with respect to pancreatic disease.…”
Section: Cigarette Smokementioning
confidence: 99%